Phylogenetic of Tapak Dara (Catharanthus roseus) Relative in Family Apocynaceae Based on matK And rbcL Sequences - Frimita Bella; Erlia Narulita; Kuswati Kuswati (Jambura Edu Biosfer Journal, 2024)
The Apocynaceae family, including Tapak Dara (Catharanthus roseus), is one of the most popular medicinal plants due to its secondary metabolites. Secondary metabolites are naturally produced in small amounts, but have very high economic value. Therefore, exploration of plant species within the same family is an interesting issue to be conducted. The purpose of this study is to discover members of the Apocynaceae family that have close relatives with Catharanthus roseus so that expected to have the similar active compounds. The method used was phylogenetic analysis using DNA sequences of maturase K (matK) and riboluse 1,5-biphosphate carboxylase/oxygenase large subunit (rbcL) regions. A total of 22 plants of the Apocynaceae family were used, and the sequences of both genes from these plants were retrieved in the NCBI database. Phylogenetic tree was constructed using MEGA 11 and two Rubiaceae species as outgroups. The study results showed that 10 plant groups were formed based on the suprageneric in both trees generated. It is consistently obtained that Rauvolfia serpentina is in one group with Catharanthus roseus in the Vinceae tribes of Rauvolfioideae subfamily. Morphologically, this group of plants has similar flower and leaf characters. It can be conclude that phylogenetic analysis with DNA sequences supports the grouping of morphological data, and indicates that R. serpentine has a biochemical profile similar to Tapak Dara.